Sleep and gastric function in irritable bowel syndrome: derailing the brain-gut axis. Issue 3 (1st September 1997) - Orr, W C; Crowell, M D; Lin, B; Harnish, M J; Chen, J D Z
Abstract : Background —Recently, several studies have shown an alteration in bowel function during sleep in patients with irritable bowel syndrome (IBS), and a recent study also suggests a remarkable increase in rapid eye movement (REM) sleep. These studies have suggested that an alteration in CNS function may play an important role in the pathogenesis of IBS. Aims —To confirm the presence of an alteration in REM sleep in patients with IBS and to assess the relation between sleep and a non-invasive measure of gastric functioning, the electrogastrogram (EGG). Patients —Ten patients with IBSand 10 age and sex matched normal volunteers. Methods —All subjects slept one night in the sleep laboratory and underwent polysomnographic monitoring to determine sleep patterns, and recording of the EGG from surface electrodes. Results —The IBS group had a notable and significant increase in the percentage and duration of REM sleep (p<0.05). The control group had a decrease in the amplitude of the dominant EGG frequency from waking to non-REM sleep (p<0.05), and a subsequent increase in the amplitude from non-REM to REM sleep (p<0.05). No such changes were noted in the patients with IBS. Conclusions —Results confirmed the enhancement of REM sleep in patients with IBS and suggested an intrinsic alteration in autonomic and CNS functioning in patients with IBS.